2013
DOI: 10.5863/1551-6776-18.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid and Topiramate Induced Hyperammonemic Encephalopathy in a Patient With Normal Serum Carnitine

Abstract: A 17-year-old female developed hyperammonemic encephalopathy 2 weeks after valproic acid (VPA), 500 mg twice a day, was added to her regimen of topiramate (TPM), 200 mg twice a day. She presented to the emergency department (ED) with altered mental status, hypotension, bradycardia, and lethargy. Laboratory analysis showed mild non-anion gap hyperchloremic acidosis, serum VPA concentration of 86 mg/L, and urine drug screen result that was positive for marijuana. She was admitted to the pediatric intensive care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…98 Concomitant use of AEDS, especially topiramate, can increase the risk of developing this complication. 99…”
Section: Valproic Acidmentioning
confidence: 99%
“…98 Concomitant use of AEDS, especially topiramate, can increase the risk of developing this complication. 99…”
Section: Valproic Acidmentioning
confidence: 99%
“…Although the use of TPM can be associated with cognitive symptoms, this side effect appears to be due to a direct effect of the drug in the CNS and is not secondary to any metabolic abnormality. Hyperammonemia secondary to the combined use of TPM and other antiepileptic drugs, particularly VPA, has been reported but is probably not common, with only a few cases reported in the literature [1–8] .…”
Section: Discussionmentioning
confidence: 99%
“…As a group, antiepileptic drugs are a relatively common cause of encephalopathy, either by direct CNS effect, or, in some cases, by inducing hyperammonemia. This is a well-established complication of valproic acid and has now been reported to occur in patients previously treated with valproic acid to which TPM was added [1–8] . Topiramate is a broad-spectrum anticonvulsant that is also extensively used for migraine prophylaxis, as a mood stabilizer, and for alcohol dependency.…”
Section: Introductionmentioning
confidence: 93%
“…Monotherapy with either valproic acid or topiramate or combination therapy with the 2 drugs has frequently been reported to cause encephalopathy. [2][3][4][5][7][8][9] In a recent retrospective chart analysis, the odds ratio for development of encephalopathy was 10 for patients receiving valproic acid -topiramate combination therapy relative to patients receiving valproic acid alone. 1 In the case reported here, the patient's improved neurologic status after withdrawal of valproic acid suggested that this drug had a role in the development of encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Certain authors have proposed that this combination evokes a synergistic mechanism that produces hyperammonemia, which in turn results in encephalopathy. 2,6 Described here is a case of encephalopathy potentially induced by the combination of valproic acid and topiramate, in which serial serum ammonia measurements suggested that encephalopathy may occur before hyperammonemia.…”
Section: Introductionmentioning
confidence: 99%